PEMBERDAYAAN MASYRAKAT MELALUI PEMBINAAN UMKM KAMPUNG BATIK BETUNGAN - Rega Anggrayani; Agus Zainal (Jurnal Pendidikan Sepanjang Hayat, 2021)
This study aims to obtain information systematically related to community empowerment through the development of UMKM in the Betungan batik village. The method used was the focus group discussion by getting the result that community empowerment through UMKM was carried out once a month, discussing the existing programs in the Betungan batik village UMKM with 50 members. UMKM Batik Betungan Village makes various products made from written batik such as batik scarves, batik bags, batik sandals, batik masks, and hand-written batik hijabs.